2013
DOI: 10.1159/000356602
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hydrogen Sulfide Protects against Doxorubicin-Induced Inflammation and Cytotoxicity by Inhibiting p38MAPK/NFκB Pathway in H9c2 Cardiac Cells

Abstract: Background/Aim:We have demonstrated that exogenous hydrogen sulfide (H2S) protects H9c2 cardiac cells against the doxorubicin (DOX)-induced injuries by inhibiting p38 mitogen-activated protein kinase (MAPK) pathway and that the p38 MAPK/nuclear factor-κB (NF-κB) pathway is involved in the DOX-induced inflammatory response and cytotoxicity. The present study attempts to test the hypothesis that exogenous H2S might protect cardiomyocytes against the DOX-induced inflammation and cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
72
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 47 publications
9
72
0
2
Order By: Relevance
“…Numerous studies have demonstrated that the primary molecular mechanism involved in DOX-induced cardiotoxicity is free radical-induced oxidative stress, and cardiomyocyte death by apoptosis and necrosis (5,22). In accordance with previous studies (23,24), in the present study it was observed that the exposure of H9c2 cells to DOX significantly induced cellular injuries, including decreases in cell viability and the expression of SIRT1, as well as increases in cell apoptosis and in the expression levels of FoxO1, P53 and Bim.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have demonstrated that the primary molecular mechanism involved in DOX-induced cardiotoxicity is free radical-induced oxidative stress, and cardiomyocyte death by apoptosis and necrosis (5,22). In accordance with previous studies (23,24), in the present study it was observed that the exposure of H9c2 cells to DOX significantly induced cellular injuries, including decreases in cell viability and the expression of SIRT1, as well as increases in cell apoptosis and in the expression levels of FoxO1, P53 and Bim.…”
Section: Discussionsupporting
confidence: 91%
“…H 2 S donors, including diallyl disulfide and S-propargylcysteine, have been shown to rescue cultured cardiomyocytes from high glycose injury, doxorubicin-induced toxicity or ROStriggered injury (Szabó et al, 2011;Guo et al, 2013;Wu et al, 2015;Yang et al, 2015). The mechanisms through which H 2 S donors have been proposed to exerts their protective effects in these cultured cell systems include ATP-sensitive potassium channel and Akt activation, inhibition of mitogen-activated protein kinases pathways (p38, c-Jun N-terminal protein kinases), and inhibition of endoplasmic reticulum stress, as well as antioxidant mechanisms (Szabó et al, 2011;Wang, 2012;Guo et al, 2013;Salloum, 2015;Wu et al, 2015;Yang Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms through which H 2 S donors have been proposed to exerts their protective effects in these cultured cell systems include ATP-sensitive potassium channel and Akt activation, inhibition of mitogen-activated protein kinases pathways (p38, c-Jun N-terminal protein kinases), and inhibition of endoplasmic reticulum stress, as well as antioxidant mechanisms (Szabó et al, 2011;Wang, 2012;Guo et al, 2013;Salloum, 2015;Wu et al, 2015;Yang Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the MAPK family, p38-MAPK and ERK1/2, are upregulated in response to cellular stress, leading to cardiomyocyte apoptosis (50,156). p38-MAPK is induced in several disease conditions including hyperglycemia, I/R injury, and hypoxia (16,49,50,134,156).…”
Section: Diabetic Cardiomyopathy Is Mitigated By H 2 S Diabetes Is Amentioning
confidence: 99%
“…p38-MAPK is induced in several disease conditions including hyperglycemia, I/R injury, and hypoxia (16,49,50,134,156). NaHS (400 M) inhibits the activation of p38-MAPK in response to the antitumor drug doxorubicin, resulting in decreased apoptosis (50).…”
Section: Diabetic Cardiomyopathy Is Mitigated By H 2 S Diabetes Is Amentioning
confidence: 99%